The #Brexit on the Facebook pages of the European institutions - Tasente, Tanase (Technium Social Sciences Journal, 2020)
The Brexit referendum was among the first major public events where online users had no "slacktivism" reactions and they led the entire debate and popular will from the inside of the online world to the real world. It is becoming increasingly clear that Social Media is becoming an increasingly powerful tool in political debates, and during the parliamentary, presidential, European parliamentary or even referendum elections, it becomes the channel that can decide the final outcome. However, the debate in the online environment can be altered by two important factors: (1) political bots - which can manipulate public opinion by posting in a large number of fake news and (2) "slacktivism" reactions from online users. , who are content only to quickly distribute unverified information or to push impulse driven on the "like" button and to scroll further. This study focused on analyzing the frequency with which European institutions spoke about Brexit on their Facebook pages and on identifying and analyzing the messages that generate high engagement from users. Thus, we will analyze all the posts published by the three major European institutions - the European Commission, the European Parliament and the Council of the European Union - starting on the first day after the Brexit Referendum in the UK (24 June 2016) until 24 June 2019.